Diagnostic Accuracy of Ortolani and Barlow Maneuvers in the Diagnosis of Developmental Dysplasia of the Hip Joint in Infants, Taking Alpha Angle on Ultrasound as a Gold Standard - Rehman, Faiza; Khan, Sabir (Biological and Clinical Sciences Research Journal, 2025)
Developmental dysplasia of the hip is a frequent cause of preventable disability if not detected early. Ortolani and Barlow maneuvers are widely used bedside screening tests, but their accuracy varies across settings. Objective: To determine the diagnostic accuracy of the Ortolani and Barlow maneuvers in the diagnosis of developmental dysplasia of the hip joint in infants, taking the alpha angle on ultrasound as a gold standard. Methods: This cross-sectional validation study was conducted on a sample of 172 infants aged 1-16 weeks, who were suspected of DDH based on risk factors such as breech presentation, family history, or in utero restriction. The researcher performed the Ortolani and Barlow maneuvers. All infants underwent a hip ultrasound conducted by an experienced radiologist who was blinded to the clinical examination. Diagnostic accuracy of the Ortolani and Barlow maneuvers was determined, along with sensitivity, specificity, positive predictive value (PPV), and and negative predictive value (NPV), by constructing a 2x2 contingency table. Results: The mean age of the infants in this study was 8.03 ± 4.53 weeks, with male gender 96 (55.8%). DDH on hip ultrasound was positive in 98 infants (57.0%), while 77 (44.8%) had positive results on the Ortolani and Barlow maneuvers. The diagnostic accuracy of Ortolani and Barlow maneuvers was 64.53%, with a sensitivity of 58.16% and a specificity of 72.97%. Conclusion: Ortolani and Barlow manoeuvres exhibited a modest diagnostic accuracy of 64.53%, with sensitivity of 58.16% and specificity of 72.97%, using the alpha angle on ultrasound as the gold standard.